Parenting Meeting Development Module - Mela Susanti; Imas Kania Rahman; Ibdalsyah Ibdalsyah (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2020)
The purpose of this research is to find out how parents were coaching activities in Raudatul Atfal (RA). Darul Muttaqien and RA. Ibn Sina. The research method used in this study is qualitative field research—data collection tool through observation, interviews and documentation. The Parenting Meeting (KPO) coaching module has been tested for validity through a Focus Group Discussion (FGD) with four experts: religious experts, linguists, psychologists and education experts. The results of this study are coaching parents in RA. Darul Muttaqien Parung has not been systematically planning on an activity program sheet. 80% of parents state that the child's development at home is the same as the school. While fostering parents in RA. Ibnu Sina Pamijahan has been going well, planned and systematic; 50% of parents statements is that the development of morals at home is not the same as the school.AbstrakTujuan penelitian ini adalah untuk mengetahui bagaimana orang tua pembinaan kegiatan di Raudatul Atfal (RA). Darul Muttaqien dan RA. Ibnu Sina. Metode penelitian yang digunakan dalam studi ini adalah penelitian lapangan kualitatif. Alat pengumpulan data melalui pengamatan, wawancara dan dokumentasi. The Parenting Meeting (KPO) modul pembinaan telah diuji untuk validitas melalui Focus Group diskusi (FGD) dengan 4 ahli: ahli agama, linguis, psikolog dan ahli pendidikan. Hasil penelitian ini adalah pembinaan orang tua di RA. Darul Muttaqien Parung belum direncanakan secara sistematis pada lembar program kegiatan. 80% orang tua menyatakan bahwa perkembangan anak di rumah sama dengan sekolah. Sementara, membina orang tua di RA. Ibnu Sina Pamijahan telah berjalan dengan baik, terencana dan sistematis, 50% dari pernyataan orang tua adalah bahwa perkembangan moral di rumah tidak sama dengan sekolah